Die Relevanz nicht-wettbewerblicher Belange im Kartellverbot: Eine Analyse anhand der Beispiele des Umweltschutzes und des Tierwohls - Friedrich, Marilena, LL. M. (London) (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The sustainability debate has also reached competition law. Companies are calling for a relaxation of the ban on cartels in order to better promote climate protection, for example. At the same time, there is a danger of greenwashing. Against this background, Marilena Friedrich deals with the admissibility of sustainability agreements using the examples of environmental protection and animal welfare. The so-called integration clauses of the TFEU require that these objectives are also taken into account in the ban on cartels. However, substantive antitrust law as well as its procedures and institutions need revising in general, as this work shows on the basis of a thorough analysis, which it combines with innovative proposals de lege ferenda.